2017
DOI: 10.1002/smll.201702616
|View full text |Cite
|
Sign up to set email alerts
|

Polyhedral‐Like NiMn‐Layered Double Hydroxide/Porous Carbon as Electrode for Enhanced Electrochemical Performance Supercapacitors

Abstract: Polyhedral-like NiMn-layered double hydroxide/porous carbon (NiMn-LDH/PC-x) composites are successfully synthesized by hydrothermal method (x = 1, 2 means different mass percent of porous carbon (PC) in composites). The NiMn-LDH/PC-1 composites possess specific capacitance 1634 F g at a current density of 1 A g , and it is much better than that of pure LDH (1095 F g at 1 A g ). Besides, the sample can retain 84.58% of original capacitance after 3000 cycles at 15 A g . An asymmetric supercapacitor with NiMn-LDH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
62
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 157 publications
(65 citation statements)
references
References 60 publications
3
62
0
Order By: Relevance
“…As the power density increases to 6286 W kg −1 , the energy density still can be retained to a value of 22 Wh kg −1 . These energy and power density values compare favorably with most of the recently reported LDH supercapacitors, such as NiAl‐LDH/rGO//Active carbon (15.42 Wh kg −1 at 230 W kg −1 ), NiMn‐LDHs/PC‐1//Active carbon (18.6 Wh kg −1 at 225.03 W kg −1 ), Co x Ni 1− x ‐LDH/CN x @NGHSs (28.9 Wh kg −1 at 1875 W kg −1 ), NiCo‐LDH (41.46 Wh kg −1 at 212.68 W kg −1 ), NiCo‐LDH/NG (31.2 Wh kg −1 at 354 W kg −1 ), CoMn‐LDH//AC (5.9 Wh kg −1 at 1000 W kg −1 ), and CoNiFe‐LDH/CNFs (30.2 W h kg −1 at 800 W kg −1 ),10a shown in Figure f.…”
Section: Resultssupporting
confidence: 79%
“…As the power density increases to 6286 W kg −1 , the energy density still can be retained to a value of 22 Wh kg −1 . These energy and power density values compare favorably with most of the recently reported LDH supercapacitors, such as NiAl‐LDH/rGO//Active carbon (15.42 Wh kg −1 at 230 W kg −1 ), NiMn‐LDHs/PC‐1//Active carbon (18.6 Wh kg −1 at 225.03 W kg −1 ), Co x Ni 1− x ‐LDH/CN x @NGHSs (28.9 Wh kg −1 at 1875 W kg −1 ), NiCo‐LDH (41.46 Wh kg −1 at 212.68 W kg −1 ), NiCo‐LDH/NG (31.2 Wh kg −1 at 354 W kg −1 ), CoMn‐LDH//AC (5.9 Wh kg −1 at 1000 W kg −1 ), and CoNiFe‐LDH/CNFs (30.2 W h kg −1 at 800 W kg −1 ),10a shown in Figure f.…”
Section: Resultssupporting
confidence: 79%
“…By virtue of large surface area and the sophisticated structural design, the UNML exposes more active sites and available space, which are beneficial to the diffusion of electrolyte ions and the kinetics of reaction, ultimately improved the electrochemical performance. [38,39] The top left inset of Figure 3d and Figure 3e show the pore size distribution curves, indicating a mean pore size of 10-20 nm and about 3.2 nm for NML and UNML. It can be predicted that NML-0.1 and NML-0.5 have lower porosity than UNML, which is confirmed by further exploration, as shown in Figure S3a-b.…”
Section: Resultsmentioning
confidence: 99%
“…For example, Yu et al reported the synthesis and capacitive behavior of NiMn LDH/PC composites. [122] PC derived from the calcination of zeolitic imidazolate frameworks-8 (ZIF-8 MOF) possesses ah igh level of porosity and retains the originalm orphology. NiMn LDH nanosheets crosslinked to each other uniformly cover the framework of PC, througha ni ns itu growth method.…”
Section: Carbon Nanoparticles (Cnps)mentioning
confidence: 99%